High Abdominal Perfusion Pressure Using Umbilical Cord Flap in the Management of Gastroschisis - Mohamed Ahmed Arafa; Khalid Mohamed Elshimy; Mohamed Ali Shehata; Akram Elbatarny; Hisham Almohamady Almetaher; Hamed Mahmoud Seleim (Frontiers Media S.A., 2021)
Background: Gastroschisis management remains a controversy. Most surgeons prefer reduction and fascial closure. Others advise staged reduction to avoid a sudden rise in intra-abdominal pressure (IAP). This study aims to evaluate the feasibility of using the umbilical cord as a flap (without skin on the top) for tension-free repair of gastroschisis.Methods: In a prospective study of neonates with gastroschisis repaired between January 2018 to October 2020 in Tanta University Hospital, we used the umbilical cord as a flap after the evacuation of all its blood vessels and suturing the edges of the cord with the skin edges of the defect. They were guided by monitoring abdominal perfusion pressure (APP), peak inspiratory pressure (PIP), central venous pressure (CVP), and urine output during 24 and 48 h postoperatively. The umbilical cord flap is used for tension-free closure of gastroschisis if PIP > 24 mmHg, IAP > 20 cmH2O (15 mmHg), APP <50 mmHg, and CVP > 15cmH2O.Results: In 20 cases that had gastroschisis with a median age of 24 h, we applied the umbilical cord flap in all cases and then purse string (Prolene Zero) with daily tightening till complete closure in seven cases, secondary suturing after 10 days in four cases, and leaving skin creeping until complete closure in nine cases. During the trials of closure, the range of APP was 49-52 mmHg. The range of IAP (IVP) was 15-20 cmH2O (11-15 mmHg), the range of PIP was 22-25 cmH2O, the range of CVP was 13-15 cmH2O, and the range of urine output was 1-1.5 ml/kg/h.Conclusion: The umbilical cord flap is an easy, feasible, and cheap method for tension-free closure of gastroschisis with limiting the PIP ≤ 24 mmHg, IAP ≤ 20 cmH2O (15 mmHg), APP > 50 mmHg, and CVP ≤ 15cmH2O.